Law Enforcement Efforts in Addressing Online Prostitution in Banda Aceh City: A Study of the Role of Satpol PP and Wilayatul Hisbah - Lajuna, Muhammad Barokah; Roslaili, Yuni; Kamaruzzaman, Yusnaidi (MAQASIDI: Jurnal Syariah dan Hukum, 2025)
This study examines law enforcement efforts against online prostitution in Banda Aceh City, carried out by the Civil Service Police Unit (Satpol PP) and the Wilayatul Hisbah (WH). This phenomenon poses a serious challenge in Aceh, a region governed by Islamic Sharia law. Employing a descriptive qualitative approach and empirical juridical method, data were collected through interviews and literature review. The findings indicate that enforcement efforts are implemented through preventive (religious education and legal socialization), repressive (field raids and monitoring), and curative (rehabilitation and moral guidance) approaches. Despite the existence of legal frameworks such as the Qanun Jinayat, enforcement faces several obstacles, including limited human resources, lack of technological support, and the absence of specific regulations addressing online prostitution. Furthermore, low public legal awareness and the evolving tactics used by perpetrators through technology create additional enforcement difficulties. Therefore, strategic steps such as regulatory reform, capacity building for law enforcement officers, institutional cooperation, and increased community participation are crucial to enhancing the effectiveness and sustainability of Sharia law enforcement in tackling online prostitution in the digital era.